A comparison of white light laryngostroboscopy versus autofluorescence endoscopy in the evaluation of vocal fold pathology. (22nd April 2013) - Caffier, Philipp P.; Schmidt, Bernd; Gross, Manfred; Karnetzky, Klaus; Nawka, Tadeus; Rotter, Andreas; Seipelt, Matthias; Sedlmaier, Benedikt
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To prove the diagnostic value of autofluorescence endoscopy (AFE) and white light laryngostroboscopy (WLS) versus the gold standard microlaryngoscopy with histopathological examination in differential diagnostics of laryngeal lesions for experienced phoniatricians and laryngologists, using the PENTAX SAFE‐3000 system. Study Design Exploratory cohort study. Methods High‐resolution rigid WLS was executed in 32 consecutive patients with initial manifestation of benign, precancerous, and malignant vocal fold lesions. Fiberoptic blue light AFE (SAFE‐3000; λ = 408 nm) was subsequently performed by an experienced endoscopist in a blinded study setting. Findings were rated based on objective WLS and AFE parameters (e.g., phonatory vibration, mucosal wave propagation, and loss of autofluorescence). The clinically assumed WLS and AFE diagnoses were compared with the final histopathology of biopsied material taken during microlaryngoscopy. Results In reference to histopathological diagnosis, WLS achieved a higher sensitivity (100% vs. 94%), specificity (94% vs. 69%), and accuracy (97% vs. 81%) than AFE diagnostics. The concordance between both endoscopic techniques was 87.5% (28/32 patients); additional AFE benefits were not detectable. Significant loss of autofluorescence was observed in malignant findings clinically clearly diagnosed by WLS, but also in chronic inflammation, severe dysplasia, granulomas, vascular polyps, and glottal papillomatosis. Conclusions The evaluation of vocal fold pathology by the clinically experienced examiner precisely applying WLS appears to be more reliable than diagnostics of mucosal tissue changes by means of AFE via the SAFE‐3000 system as a relatively nonspecific method. Microlaryngoscopy with histopathological examination and phonomicrosurgical excision of pathologic changes remains the gold standard. Laryngoscope, 2012